Piglet enterprise assessment and improvement in Cat Que Commune, Vietnam - Peters, D.; Nguyen, TS; Nguyen, BM; Pham, NT (2004)
The mainstay of economic activity in Cat Que Commune, Hoai Duc District of Ha Tay Province in Vietnam is got raising, which is the production of piglets between 8 to 30 kg, filling a gap between the sow/piglet and meat pig productions. A cluster of associated enterprises have developed around this got-based enterprise which include the got raisers, piglet suppliers, feed and medicine suppliers, veterinarian services, got collectors, and manure collectors. The relationships with these associated enterprises form the basis of the complex enterprise strategies of the got raisers, which strive to balance a complex set of issues of feed, growth, season, disease control, labour, credit, and marketing in order to ensure the profitability and sustainability of the enterprise.